CLASSIFICATION OF NON-CORONARY HEART DISEASES. POINT OF VIEW - O. V. Blagova; A. V. Nedostup (Российский кардиологический журнал)
The problem of non-coronary diseases of myocardium (NCDM) and, particularly, the classification of them, is one of the most complicated in cardiology and internal medicine. Until recently, there is no unified official classification in Russia, and there are various in use for practical and scientific purposes: American (2006), European (2008) and the latest issue by Paleev N.R. and Paleev F.N. (2008). The article critically examines and compares these classifications. The analysis provided, of evolution of the term “cardiomyopathy” (CMP), European and Russian classifications of myocarditis and MOGE(S) of 2014; the principles for an “ideal” classification are proposed, at modern stage, and our original synthetic variant.Main aspects of the proposed classification are introduction of syndromal approach (the selection of primary clinical syndrome) as a first step of nosological diagnostics when NCDM suspected; retaining of nosological principle with distinction of NCDM to myocarditis, CMPs and myocardiodystrophies; selection of combination NCDM; parallel application of etiological (incl. genetic) and structure-functional CMP classification; selection of CMP with mostly right chambers lesion; selection (together with genetic and idiopathic) of the special CMPs, showing combinational nature; combinations of non-rheumatic myocarditis with peri- and endocarditis; the grade of myocardium diagnosis reliability (if biopsy impossible) with the original criteria of its diagnostics; the level of myocarditis activeness — histological and immune; two types of infarction-like myocarditis (as well as ischemic); paraneoplastic myocarditis and myocarditis as non-classified (latent) systemic immune disorder; introduction of a detailed morpho- and virological characteristics of myocarditis into classification; distinction of myocardiodystrophies by the level of systolic function compensation; creation of clinical classification of arrhythmogenic right ventricle dysplasia and non-compaction myocardium syndrome (incl. in the presence and absence of myocarditis).